Quinceañera - Glatzer, Richard 1952-2015 (Sony Pictures Home Entertainment, 2006)
On the evening before Magdalena's 15th birthday Quinceañera celebration, she discovers that she's pregnant. Forced by her family to leave her home, she moves in with her uncle and gay cousin
DVD, region 1 ; Dolby Digital 5.1 surround. - Originally released as a motion picture in 2006. - "Mastered in high definition"--Container. - Special features: optional commentary with filmmakers and cast; "On the red carpet with Quinceañera" Los Angeles premiere featurette (2 min.); "Making of Quinceañera" (21 min.); "Mis quince años" bonus scene (3 min.)
Emily Rios, Jesse Garcia, Chalo Gonzalez, Jesus Castaños-Chima, Johnny Chavez, J.R. Cruz, Araceli Guzmán-Rico, David Ross, Teresa-Michelle Ruiz, Jason L. Wood
Director of photography, Eric Steelberg ; editors, Robin Katz, Clay Zimmerman ; music, Micko, Victor Bock ; costume designer, Jessica Flaherty
Keywords: Quinceañera (Social custom) / Drama; Hispanic American teenage girls / Drama; Teenage pregnancy / Drama; Gay men / Drama; Muchachas adolescentes / Teatro; Embarazo / Teatro